Glycol losses calculation in a gas dehydration unit - Indarti, Adrian; Nugroho, Nur Khozin Adi; Zaini, Agung Rizki (Gema Wiralodra, 2023)
The gas dehydration process separates gas from water content by mixing absorbents such as glycol in the gas dehydration unit. The gas dehydration process can use triethylene glycol type glycol, reducing the water content to a minimum of 7 lb/mmscfd. In the dehydration process, glycol losses will usually occur either in the reboiler or contactor; for this reason, this study aims to determine the causes of glycol losses, calculate the water content absorbed in the contactor, determine the percentage of glycol losses and calculate how much glycol is needed in each 1mmscfd of gas. Glycol losses are classified into two types: expected and up-standard. In this case, the research method starts by calculating the amount of water content that can be absorbed, the percentage of glycol losses, and the amount of glycol volume required in every one mmscfd of gas. Causes of glycol losses include the number of trays, contact time, absorption surface area, flow rate, and temperature in the reboiler. Of the 60.96 mmscfd of wet gas that entered the contactor, it was found that 32.11 lb/mmscfd of water managed to absorb glycol. Based on the calculation of glycol losses in some test data, the average glycol losses (0.087 gal/mmscf) are still categorized as ordinary losses because the glycol losses that occur do not exceed the safe limit set by the industry, which is 0.01 – 0.15 gal /mmscf. One way to reduce the occurrence of glycol losses is to adjust the pump discharge to the incoming gas flow so that excess glycol is not used when there is contact between glycol and wet gas.